Fixer [videorecording (DVD)] : the taking of Ajmal Naqshbandi - Olds, Ian; Olds, Ian; Parenti, Christian (Cinema Guild, 2009)
Examines the life and death of Ajmal Naqshbandi, held hostage in Afghanistan with journalist Christian Parenti, while Ajmal was working as Christian's "fixer". The documentary details the hazards of the fixer's job, which involves translation, providing transport, arranging meetings with local sources, and alerting the fixer's employer to various dangers. After Ajmal is captured with Christian by local Talibas forces, Parenti is eventually released, while Ajmal is forced to stay. Accompanying these events, the film explores the botched hostage negotiation, government corruption, and the relationship between journalists and their translators.